Exploring the impact of integrating HR practices and MIS on employee engagement and productivity in the retail banking division of the City Bank - Riya, Rounak Jahan (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.